Prognostic Value of CD63 Expression in Solid Tumors: A Meta-analysis of the Literature - KOH, HYUN MIN (In Vivo, 2020)
Background: CD63 has been described as a key factor in extracellular vesicle production and endosomal cargo sorting, and there have been certain reports suggesting an association between CD63 expression and survival in patients with tumors including gastric, colon and lung cancer. However, the prognostic value of CD63 expression remains contradictory. Hence, we performed this meta-analysis to assess the prognostic value of CD63 expression in solid tumors. Materials and Methods: Eligible studies were collected by searching the PubMed, Embase and Cochrane libraries. The hazard ratio (HR) with 95% confidence interval (CI) were evaluated to reveal the association between CD63 expression and survival in solid tumors. Results: Five studies with a total of 1,454 patients were included. The HR evaluating CD63 expression on survival was 1.34 (95%CI=0.92-1.97, p=0.129). In subgroup analysis, the HRs of lung cancer and other tumors were 0.50 (95% CI=0.32-0.77, p=0.002) and 2.16 (95% CI=1.93-2.42, p<0.001) respectively. CD63 expression was significantly associated with poor disease-specific survival (HR=1.69, 95% CI=1.15-2.49, p=0.008), but not with disease–free survival and overall survival. Also, there was a significant association between CD63 expression with poor survival in the group of sample size more than 150 patients (HR=2.15, 95% CI=2.92-2.41, p<0.001), but not in the group of sample size with fewer than 150 patients. Conclusion: This meta-analysis suggested that CD63 expression may be a potential prognostic marker in solid tumors.